2007
DOI: 10.1196/annals.1397.090
|View full text |Cite
|
Sign up to set email alerts
|

Immunomorphological Analysis of RAGE Receptor Expression and NF‐κB Activation in Tissue Samples from Normal and Degenerated Intervertebral Discs of Various Ages

Abstract: We immunohistochemically investigated the pattern of RAGE expression and NFkappaB translocation into the nucleus in 43 complete cross-sections of human lumbar intervertebral discs (neonatal-85 years) and compared this with the carboxymethyl-lysine (CML) modification of proteins as a marker for oxidative stress. No significant expression of RAGE, no obvious activation of NF-kappaB, and no deposition of CML-modified proteins were seen in fetal, juvenile, and young adolescent discs (until age of 13 years). In adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 15 publications
3
96
0
1
Order By: Relevance
“…In recent years, numerous studies have demonstrated that oxidative stress plays an important role in the initiation and progression of disk degeneration. [16][17][18][19][20][21][22][23][24][25][26] These reports led us to seek an antioxidative therapy for alleviating oxidative stress on cells that may allow a slow but controlled regeneration of disk. The purpose of the present study was to investigate the potential therapeutic effects of an antioxidant compound on disk degeneration in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, numerous studies have demonstrated that oxidative stress plays an important role in the initiation and progression of disk degeneration. [16][17][18][19][20][21][22][23][24][25][26] These reports led us to seek an antioxidative therapy for alleviating oxidative stress on cells that may allow a slow but controlled regeneration of disk. The purpose of the present study was to investigate the potential therapeutic effects of an antioxidant compound on disk degeneration in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In disk tissues, oxidative stress may initiate or participate in matrix destruction and cell apoptosis, which ultimately result in disk degeneration. 16 It has been shown that the increase of exogenous NO may promote cell apoptosis and suppress proteoglycan synthesis in cultured disk cells. NO has been demonstrated to participate in the disk degeneration induced by mechanical stress or interleukin (IL)-1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is a known driver of cellular senescence and apoptosis. Higher levels of oxidized proteins and transcription factors activated by oxidative stresses have been found in older discs compared with young discs [64]. Other evidence of age-related oxidative damage in the disc is the presence of advanced glycalation endproducts, which are molecules produced by nonenzymatic glycosylation and oxidation of proteins and lipids [6,83].…”
Section: Aging and Oxidative Stressmentioning
confidence: 99%
“…Furthermore, more "modern" pharmaceuticals, such as the COX-2 inhibitor rofecoxib, can infl uence NF-B activity, e.g. in this case by inhibiting its DNA binding capacity (Niederberger et al, 2003). On the other hand, there are multiple "natural" candidates that seem to inhibit NF-κB in certain cell types, such as resveratrol (a polyphenol found in wine) (Holmes-McNary and Baldwin, 2000), curcumin (the main component of curcuma) (Jobin et al, 1999;Surh et al, 2000) or capsaicin (found in red pepper) (Surh et al, 2000).…”
Section: Inhibition/therapymentioning
confidence: 99%